INTEREST GROUP SESSION - BEHAVIORAL INTERVENTIONS FOR OLDER ADULTS: EASIER SAID THAN DONE: CONSIDERATIONS FOR IMPLEMENTING PRAGMATIC TRIALS. (11th November 2018) - Gaugler, J E; Gitlin, L; Mitchell, S
Abstract: Gerontological science continues to place randomized controlled trials (RCTs) at the apex of evidence. However, the time, expense, and inordinate focus on efficacy in RCTs have led to their inconsistent influence on clinical decisions or practice. In response to these concerns, many researchers have advocated for pragmatic trials. Pragmatic trials aim to include populations that are most likely to receive a given intervention in routine practice, feature control groups that will receive an appropriate standard of care, and incorporate outcomes that are important to key stakeholders. This symposium features the challenges and lessons learned in implementing a pragmatic trial that is currently evaluating the effectiveness, cost benefit and implementation potential of a novel family caregiver support program (ADS Plus) embedded in 30 adult day programs throughout the U.S. Symposium presentations will begin with a brief overview of the ADS Plus project by Laura Gitlin, PhD. Joseph E. Gaugler, PhD and David L. Roth, PhD will follow with a summary of methodological considerations when implementing the ADS Plus pragmatic trial. Katherine Marx, PhD, will describe the enrollment process and baseline data collection successes and challenges. Lauren Mitchell, PhD and colleagues will then review the stakeholder engagement process that has taken place during the ADS Plus trial. Keith Anderson, PhD and Holly Dabelko-Schoeny, PhD will provide perspectives of participating programs in the ADS Plus trial. Susan Mitchell, PhD, an expert in the conduct of pragmatic trials across the long-term care spectrum, will serve as the discussant.